2021
DOI: 10.1108/aaaj-08-2020-4794
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and global clothing retailers' responsibility to vulnerable workers: NGO counter-rhetoric

Abstract: PurposeThis article aims to examine how non-governmental organisations (NGOs)' narratives portray the vulnerability of workers in global clothing supply chains during the COVID-19 crisis.Design/methodology/approachThe research analyses the rhetoric in global clothing retailers' and NGOs' counter-rhetoric during the first seven months of 2020.FindingsDuring this period, retailers employed rhetorical strategies to legitimise irresponsible actions (corporate hegemony prevailed), while NGOs embraced forms of count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Only a few accountability studies focus on the not-for-profit sector. Haque et al (2022), for example, noted the role of NGOs in identifying inadequate accountability practices in the fashion retail industry in the times of crises. Finchum-Mason et al (2020) surveyed charity officials and found that philanthropic foundations were responsive to the pandemic, with grantee relationships being affected the most.…”
Section: Ingos' Practices Of Being Accountable Onlinementioning
confidence: 99%
“…Only a few accountability studies focus on the not-for-profit sector. Haque et al (2022), for example, noted the role of NGOs in identifying inadequate accountability practices in the fashion retail industry in the times of crises. Finchum-Mason et al (2020) surveyed charity officials and found that philanthropic foundations were responsive to the pandemic, with grantee relationships being affected the most.…”
Section: Ingos' Practices Of Being Accountable Onlinementioning
confidence: 99%
“…the State and international governmental bodies) and micro (e.g. the corporation) level actors to account (Ahmad et al , 2022). This paper focuses on the micro-rhetoric of Chevron Australia and its protagonist, the ITF, as the language or discourse designed to persuade.…”
Section: Rhetorical Analysismentioning
confidence: 99%
“…However, while rhetoric is often regarded as deceptive, it can also provide a solution or give detractors the opportunity to challenge dominant positions or arguments (Young, 2003). For example, Ahmad et al (2022) highlight the use of counter rhetoric by NGOs to expose neoliberal justifications for questionable corporate practices. Despite rhetoric being a well-established method, in-depth analyses to understand the construction of Aristotelian appeals at a micro level are limited (Gelmini et al , 2021).…”
Section: Rhetorical Analysismentioning
confidence: 99%
“…One study found that in the UK, traditional public accountability of the government was suspended but replaced by informal forms of accountability facilitated by active and engaged civil society actors (Sian and Smyth, 2021). Similarly, during the emergency, counter-accounts by NGOs provided a tool to expose the rhetoric of fashion retailers and expose injustice to vulnerable workers (Ahmad et al , 2022). In the same context, Li et al (2021) found that political, organizational and moral forms of accountability developed in the garment industry via a digital platform that allowed for an open dialogue and created more awareness about human rights.…”
Section: Background Literaturementioning
confidence: 99%